Comparing food desert residents with non-food desert residents on grocery shopping behaviours, diet and BMI: results from a propensity score analysis. Issue 5 (20th April 2020) - Woodruff, Rebecca C; Haardörfer, Regine; Raskind, Ilana G; Hermstad, April; Kegler, Michelle C
Abstract: Objective: To determine whether residence in a US Department of Agriculture-designated food desert is associated with perceived access to healthy foods, grocery shopping behaviours, diet and BMI among a national sample of primary food shoppers. Design: Data for the present study came from a self-administered cross-sectional survey administered in 2015. Residential addresses of respondents were geocoded to determine whether their census tract of residence was a designated food desert or not. Inverse probability of treatment-weighted regression was used to assess whether residence in a food desert was associated with dependent variables of interest. Setting: USA. Participants: Of 4942 adult survey respondents, residential addresses of 75·0 % ( n 3705) primary food shoppers were included in the analysis. Results: Residence in a food desert (11·1 %, n 411) was not significantly associated with perceived access to healthy foods, most grocery shopping behaviours or dietary behaviour, but was significantly associated with primarily shopping at a superstore or supercentre v . a large grocery store (OR = 1·32; 95 % CI 1·02, 1·71; P = 0·03) and higher BMI ( b = 1·14; 95 % CI 0·36, 1·93; P = 0·004). Conclusions: Results suggest that food desert residents shop at different food stores and have higher BMI than non-food desert residents.